Increased risk of hospital admission for dehydration or heat‐related illness after initiation of medicines: a sequence symmetry analysis. (4th July 2016) - Kalisch Ellett, L. M.; Pratt, N. L.; Le Blanc, V. T.; Westaway, K.; Roughead, E. E.
Summary: What is known and objective: Although several studies have identified factors which increase the risk of heat‐related illness, few have assessed the contribution of medicines. To address this knowledge gap, our study aimed to assess the risk of hospital admission for dehydration or other heat‐related illness following initiation of medicines. Methods: We conducted a retrospective analysis using prescription event symmetry analysis (PESA) of 6700 veterans with incident hospital admission for dehydration or heat‐related illness (ICD‐10‐AM codes E86, X30, T67), between 1 January 2001 and 30 June 2013. The main outcome measure was first ever hospital admission for dehydration or heat‐related illness following initiation of commonly used medicines. Results and discussion: A significantly higher risk of incident hospital admission for dehydration or heat‐related illness was observed following initiation of anticoagulants, cardiovascular medicines, NSAIDs, antipsychotics, antidepressants and anticholinergic agents. The risk of hospital admission for dehydration or heat‐related illness ranged from 1·17 (SSRIs) to 2·79 (ACEI plus diuretic combination product). No significant association was observed between initiation of anticonvulsants, anti‐Parkinson's agents, hypnotics, anxiolytics or antihistamines and hospital admission for dehydration or heat‐related illness. What is new and conclusion: Many commonly used medicines were found to be associated with increased risk of hospitalization for dehydration or heat‐related illness. Initiation of ACE inhibitors in combination with diuretics had the highest risk. Prescribers and patients should be aware of the potential for medicines to be associated with increased risk of dehydration and heat‐related illness. Abstract : Hospital admission for dehydration or heat‐related illness was found to be associated with initiation of many commonly used medicines including anticoagulants, nitrates, diuretics, beta blockers, calcium channel blockers, ACEI or ARB (in combination with a diuretic or alone), NSAIDs, antipsychotics, antidepressants and anticholinergic medicines. The risk was highest following initiation of ACEI in combination with a diuretic. Prescribers and patients should be aware of the potential for medicines to be associated with increased risk of heat‐related illness, particularly during periods of hot weather.